Prospective elementary teachers' abilities in tackling a contextualized physics problem as guided inquiry - García-Carmona,Antonio (2020)
Abstract This article presents a qualitative study, with a descriptive and interpretative nature, of the abilities of prospective elementary teachers (PETs) to solve a contextualized problem of physics through a process of guided inquiry. Specifically, an analysis was made of the PETs' abilities to (a) formulate hypotheses; (b) plan inquiry procedures aimed at testing hypotheses; and (c) draw conclusions from the inquiry (i.e., interpret experimental data to accept or reject their hypotheses, and recognize the limitations of the inquiry that they had conducted). The study participants were 17 PETs who were receiving training in science teaching. They were organized into small groups to solve the physics problem proposed to them. The study's data were extracted from the inquiry reports that the groups prepared by following a script with open-ended questions. The results revealed the PETs' strengths and weaknesses in addressing the different scientific practices that had been required in the process, as well as showing that they all had achieved some improvement in their inquiry abilities after completing the activity. A discussion of the results is given with a view to improving the training of PETs in inquiry-based science learning.